Learning Videos Increase Students' Cognitive Learning Outcomes on Animal Life Cycle Materials - Indria Adi Kuncoro; Yulia Maftuhah Hidayati (Jurnal Ilmiah Sekolah Dasar, 2021)
Learning media has an important role in the implementation of learning in the current era of globalization. Therefore, we need an interactive learning media that can improve student learning outcomes. This study aims to improve students' cognitive learning outcomes on animal life cycle material using video learning on animal life cycle material for fourth grade students. This research is a classroom action research (CAR) which adapts the CAR model from Kemmis and McTaggart. The subjects in this study were grade IV students, totaling 33 students. Data was collected using an instrument in the form of a cognitive test of learning outcomes. The data that has been collected is then analyzed using a comparative descriptive method, namely by comparing the results from the pre-cycle stage to the second cycle. The results showed that the average score of students in the pre-cycle was 72 (33%) and the average in the first cycle was 80.30 (76%) and the second cycle average was 91.21 (90%). Based on these results, it can be concluded that the use of learning videos can improve students' cognitive learning outcomes for animal life cycle materials.